Selective digestive decontamination solution used as "lock therapy" prevents and eradicates bacterial biofilm in an in vitro bench-top model - María Jesús Pérez-Granda; Beatriz Alonso; Ricardo Zavala; María Consuelo Latorre; Javier Hortal; Rafael Samaniego; Emilio Bouza; Patricia Muñoz; María Guembe (BMC, 2020)
Abstract Background Most preventing measures for reducing ventilator-associated pneumonia (VAP) are based mainly on the decolonization of the internal surface of the endotracheal tubes (ETTs). However, it has been demonstrated that bacterial biofilm can also be formed on the external surface of ETTs. Our objective was to test in vitro the efficacy of selective digestive decontamination solution (SDDs) onto ETT to prevent biofilm formation and eradicate preformed biofilms of three different microorganisms of VAP. Methods We used an in vitro model in which we applied, at the subglottic space of ETT, biofilms of either P. aeruginosa ATCC 15442, or E. coli ATCC 25922, or S. aureus ATCC 29213, and the SDDs at the same time (prophylaxis) or after 72 h of biofilm forming (treatment). ETT were incubated during 5 days with a regimen of 2 h-locks. ETT fragments were analyzed by sonication and confocal laser scanning microscopy to calculate the percentage reduction of cfu and viable cells, respectively. Results Median (IQR) percentage reduction of live cells and cfu/ml counts after treatment were, respectively, 53.2% (39.4%-64.1%) and 100% (100%-100.0%) for P. aeruginosa, and 67.9% (46.7%-78.7%) and 100% (100%-100.0%) for E. coli. S. aureus presented a complete eradication by both methods. After prophylaxis, there were absence of live cells and cfu/ml counts for all microorganisms. Conclusions SDDs used as "lock therapy" in the subglottic space is a promising prophylactic approach that could be used in combination with the oro-digestive decontamination procedure in the prevention of VAP.